2007
DOI: 10.2319/022406-79
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength Comparison between Two Orthodontic Adhesives and Self-Ligating and Conventional Brackets

Abstract: All three groups demonstrated clinically acceptable bond strength. The Damon 2 self-ligating bracket exhibited satisfactory in vitro bond strength with both adhesive systems used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 12 publications
4
32
3
6
Order By: Relevance
“…Transbond XT adhesive, a composite resin, was chosen as one of the controls due to its popularity and common use in other bond strength studies. 7,8 Similar to the claims made by the ACP-adhesive manufacturer, the use of resin-modified glass ionomer cement (Fuji Ortho LC) has been said to be more effective in preventing white spot lesions than conventional composite resins. 9 Using this cement as another comparative group allows comparison of adhesives marketed for the purpose of white spot prevention.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Transbond XT adhesive, a composite resin, was chosen as one of the controls due to its popularity and common use in other bond strength studies. 7,8 Similar to the claims made by the ACP-adhesive manufacturer, the use of resin-modified glass ionomer cement (Fuji Ortho LC) has been said to be more effective in preventing white spot lesions than conventional composite resins. 9 Using this cement as another comparative group allows comparison of adhesives marketed for the purpose of white spot prevention.…”
Section: Introductionmentioning
confidence: 76%
“…A storage time of 40 hours was chosen since short times in excess of 24 hours are not critical 10 and also to remain consistent with previous studies using Transbond XT as a control. 8,11 An Instron universal testing machine (Instron Corp, Canton, Mass) was used to debond the brackets using a shear load applied to the bracket at a crosshead speed of 0.1 mm/min. Specimens were positioned in the Instron machine in a manner such that the loading force was directed parallel to the long axis of the tooth and contact was made as close to the bracket/tooth interface as possible.…”
Section: Mounting and Shear Bond Testing Proceduresmentioning
confidence: 99%
“…Vicente et al suggested use of TPCCA along with TSEP/TMIP if there is a risk of contamination with water or saliva. Northrup et al 20 have reported clinically acceptable SBS of a similar color changing adhesive 'bluegloo' (Ormco Corp) with self-ligating bracket in comparison with Transbond XT bonded to self-ligating bracket and conventional stainless steel bracket. Bluegloo also posses the property of color change with temperature retaining blue color in cooler temperature and changes to tooth color with activation by light.…”
Section: Discussionmentioning
confidence: 99%
“…This type of bond failure was preferable because less risk of enamel damage during debonding. 9 It was recommended to have a resin remnant on the tooth surface after debonding to prevent enamel crazing or fracturing. 10 Furthermore, the results of dental disclosing solution application in ARI were consistent with intra-operator and inter-operator reliability of photograph assessment.…”
Section: Discussionmentioning
confidence: 99%